2015
DOI: 10.1007/s11356-015-5406-6
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting PM10 in Algiers: efficacy of multilayer perceptron networks

Abstract: Air quality forecasting system has acquired high importance in atmospheric pollution due to its negative impacts on the environment and human health. The artificial neural network is one of the most common soft computing methods that can be pragmatic for carving such complex problem. In this paper, we used a multilayer perceptron neural network to forecast the daily averaged concentration of the respirable suspended particulates with aerodynamic diameter of not more than 10 μm (PM10) in Algiers, Algeria. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…ANN model slightly underestimates NO 2 and PM 10 under high concentrations. In general, the performance of ANN model developed in our study is statistically comparable with previous studies (Abderrahim et al, 2016;Fernando et al, 2012;Grivas and Chaloulakou, 2006;He et al, 2013;Hooyberghs et al, 2005;Liu et al, 2015;Yu et al, 2008). The good performance of ANN model is the base for quantifying the contribution of different factors to day-to-day variations of pollutant concentrations.…”
Section: Training and Validating Of Ann Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…ANN model slightly underestimates NO 2 and PM 10 under high concentrations. In general, the performance of ANN model developed in our study is statistically comparable with previous studies (Abderrahim et al, 2016;Fernando et al, 2012;Grivas and Chaloulakou, 2006;He et al, 2013;Hooyberghs et al, 2005;Liu et al, 2015;Yu et al, 2008). The good performance of ANN model is the base for quantifying the contribution of different factors to day-to-day variations of pollutant concentrations.…”
Section: Training and Validating Of Ann Modelsupporting
confidence: 91%
“…Previous studies revealed that the statistical performance of ANN air quality model is 0.6-0.9 for R (Abderrahim et al, 2016;Fernando et al, 2012;Grivas and Chaloulakou, 2006;He et al, 2013;Hooyberghs et al, 2005;Liu et al, 2015;Yu et al, 2008). The statistical performance of ANN model depends on selected predictors, pollutant categories, the backward concentration level, pollution characteristics (regional or local), time scale (hourly or daily), and ANN structures.…”
Section: Artificial Neural Networkmentioning
confidence: 98%
“…e multilayer perceptron (MLP) architecture is one of the cases of study of this work because it is one of the most popular architectures today for PM10 forecast [13][14][15][16][17]. MLP usually consists of an input layer, one or two hidden layers, and an output layer.…”
Section: Multilayer Perceptronmentioning
confidence: 99%
“…A number of works have been dedicated to air quality modelling. Some articles refer to prediction of particulate matter and gas pollution (Abderrahim et al, 2016;Kukkonen et al, 2003;Pawul and Śliwka, 2016). A review of the research in that field was published by Rybarczyk and Zalakeviciute (Rybarczyk and Zalakeviciute, 2018).…”
Section: Introductionmentioning
confidence: 99%